PENGEMBANGAN E-MODUL BERBASIS MICROSITE DENGAN PENDEKATAN DEEP LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH PADA MATERI STATISTIKA - Wiranda Elfani; Marhadi Saputro; Dwi Oktaviana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to develop a microsite-based e-module with a deep learning approach to improve problem-solving skills in statistics material for eighth-grade junior high school students. The research method used was Research and Development (R&D) with the ADDIE development model. Data collection techniques in this study included indirect communication techniques in the form of validation sheets, teacher and student response questionnaires, and measurement techniques through posttests. The research sample consisted of 31 students from class VIII A at SMP Negeri 13 Kota Pontianak. The results showed that the developed microsite-based e-module achieved a very valid category, with a material expert validation percentage of 89% and a media expert validation percentage of 94.6%, resulting in an average score of 91.8%. In addition, the e-module was categorized as very practical, with teacher response percentages of 95% and student responses of 92.1%. Based on the posttest results, the effectiveness percentage reached 80.6%, indicating that the e-module was categorized as effective. Therefore, the microsite-based e-module with a deep learning approach is considered feasible for use in the learning process at school.